Common Units for Clotting Factors Assayed Against Different Standards - North, W R S; Stirling, Y; Meade, T W (Thrombosis and Haemostasis, 1982)
There are no generally accepted units for clotting factors except factor VIII. Results are usually expressed as percentages of the standards used in the assays and standards vary in their potency. Over a six year period, factors V, VII and VIII were measured in over 3000 participants in the Northwick Park Heart Study. Six different standards had to be used. For comparative purposes, all results were expressed in terms of the first standard (71/11). This paper describes how appropriate conversion values were derived. Three different methods were compared. One consisted of the assay of each standard against its replacement. Another was based on the use of a reference plasma spanning the use of two successive standards. The third was a population-based, or epidemiological method using the data from all the participants in the study. This method is based on the assumption that results would be the same in comparable groups of study participants. In order to ensure comparability, personal characteristics which affect clotting factor levels, such as age and degree of obesity, were taken into account. The three methods gave similar results but the population method was, in general, the most satisfactory for factor VIII as well as factors V and VII, and has been adopted for routine use.
Keywords: Coagulation standards; Epidemiology; Measurement units